Recurrent abdominal pain: a psychogenic disorder?. Issue 11 (November 1983) - McGrath, P J; Goodman, J T; Firestone, P; Shipman, R; Peters, S
Abstract : A controlled study of 30 children with recurrent abdominal pain and 30 pain free children failed to show any statistically significant differences between the groups on a variety of psychological variables thought to be associated with psychogenicity. A psychogenic basis has often been assumed as the cause in diagnosis of recurrent abdominal pain when clinical examination and laboratory tests show no organic or medical reason. We emphasise that establishing a psychogenic cause is only indicated where there is positive evidence for psychological factors such as family or school stress, extreme personality characteristics, or modelling of family pain behaviour.